Moderate Exercise Reduces Food Consumption in Obese Mice for Activate Jak-2/Stat-3 Pathway in the Hypothalami - Moura, Leandro P. [UNESP]; Marinho, Rodolfo [UNESP]; Ropelle, Eduardo R.; Cintra, Dennys E.; Souza, Claudio T.; Silva, Adelino S.; Rodrigues, Barbara A.; Pauli, Luciana S.; Pauli, Jose Rodrigo (Lippincott Williams & Wilkins, 2014)
It is very known that due to inflammatory processes the obesity leads to resistance to leptin, it reduces phosphorylation via JAK-2/STAT-3, which generates lower STAT-3 activity in the cell nucleus, and it leads to decrease the number of transcription of anorexigenic neurons (POMC/CART) and allowing transcription of orexigenic (NPY/AgRP). PURPOSE: The present study aimed to evaluate the effects of moderate aerobic training on food intake of obese mice through analysis of activity of hypothalamic proteins JAK-2/STAT-3. METHODS: It were used 30 Swiss mice (30 days old) divided into 3 groups: Control Group (C): sedentary animals fed with balanced diet ; Obese (OB) sedentary animals fed with high-fat diet throughout the experiment and Trained Obese (TOB) : animals fed with high fat diet throughout the experiment , kept sedentary during the first half of the experiment (8 weeks) and submitted to physical training protocol during the second half of the experiment (8 weeks). The exercise program consisted of treadmill running 1h, 5 days/week during 8 weeks at a speed equivalent to 60 % of maximum potency determined at the beginning of training period. To assess the leptin resistance, after rats were deprived of food for 6h with free access to water, they received i.p injection with leptin (2.0µl, 10-6M), after this, the chow was returned and food intake was determined by measuring the quantity and Kcal consumed at the end of 2h. The hypothalami was removed for determination of JAK-2 and STAt-3 activity. RESULTS: Our results showed that moderate physical exercise was effective in improving the JAK/STAT signaling pathway in the hypothalamus of obese animals. This has made these obese animals had reduced food intake and consequently lower body mass gain. CONCLUSION: It can be concluded that physical exercise, for restoring leptin signaling in the hypothalamus, controls the synthesis of neurons responsible for appetite and thus is an important tool in the treatment of obesity.